THE EFFECT OF PREGNANCY NUTRITIONAL CONSUMPTION IN LOW BIRTH WEIGHT RISK: A NARRATIVE REVIEW - Sania Yulianti; Gian Cipta G; Ikhsan Hafidz; Shafira Rizki A; Siti Nur Fatimah; Nursiswati Nursiswati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2020)
Low birth weight are conditions for babies born weighing less than 2500 grams. LBW is related to the nutrition of pregnant women obtained from the consumption of nutrition during pregnancy and nutrition of the mother before pregnancy. A well-nourished mother before and during pregnancy has a high probability of giving birth to a healthy baby, full term and normal birth weight. LBW is the highest predictor of infant mortality. The purpose of this literature is to determine how the influence of nutritional consumption of pregnant women on the risk of LBW. The method used is narrative review with the database used is Google Scholar, Pubmed and EBSCO. Keywords using Indonesian, pregnant women, low birth weight babies and English keywords, nutrients, pregnancy, low birth weight. Articles are sorted based on the author's critical analysis. There were 5 articles that explained that the nutritional consumption of pregnant women needs to pay attention to a proper diet and diet where the nutritional composition must be complete and sufficient so as to minimize the risk of LBW. The conclusion is that the consumption of nutrition of pregnant women with proper diet and diet can minimize LBW so that the recommendation for pregnant women is to fulfill the nutritional needs completely and adequately.